2008
DOI: 10.3917/reco.591.0051
|View full text |Cite
|
Sign up to set email alerts
|

L'analyse de la monnaie et de la finance par David Hume

Abstract: Résumé De l’apport de David Hume à l’analyse économique, un aspect est généralement retenu : son approche présumée quantitative de la monnaie. Or, lorsqu’on resitue l’examen des relations monétaires et financières à l’intérieur de son corpus philosophique, il révèle d’autres perspectives. Selon Hume, le processus de civilisation institue certaines fictions, qui permettent aux individus de forger un ordre symbolique. Dans une économie de marché, la distinction entre la monnaie – de nature conventionnelle – et l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Cantillon might be suspected of having adopted the metallism view. Caffentzis (2001Caffentzis ( , 2008, Wennerlind (2001Wennerlind ( , 2008 and Desmedt (2008) have accurately shown that Hume adopted the convention view. It may be added that, once the specie regime is supposed, the introduction of cost-of-production theory does not necessarily equate to unconditional support of the metallism view.…”
Section: Hume's Models Of Exogenous and Endogenous Moneymentioning
confidence: 99%
See 2 more Smart Citations
“…Cantillon might be suspected of having adopted the metallism view. Caffentzis (2001Caffentzis ( , 2008, Wennerlind (2001Wennerlind ( , 2008 and Desmedt (2008) have accurately shown that Hume adopted the convention view. It may be added that, once the specie regime is supposed, the introduction of cost-of-production theory does not necessarily equate to unconditional support of the metallism view.…”
Section: Hume's Models Of Exogenous and Endogenous Moneymentioning
confidence: 99%
“…234–235) indicates that Hume's analysis of bank issuing fits into the model with an artificial and exogenous expansion of money. Desmedt (, pp. 18–19) links Hume's opinion on bank notes with the monetary disorder in Scotland during the 1750s.…”
mentioning
confidence: 99%
See 1 more Smart Citation